Examining the Ethical Dimensions of Asset Seizure in Credit Transactions: A Study from the Perspective of Islamic Law - Ana Sriekaningsih; Vita Briliana; Loso Judijanto; Rokhimah Rokhimah; Swadia Gandhi Mahardika; Us Us Surya Nopendi; Yusniar Yusuf Ibrahim (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to examine the ethical dimensions of asset repossession practices in credit sales from the perspective of Islamic law. In the context of Islamic law, credit transactions must adhere to principles of justice, honesty, and transparency, where the repossession of goods by the seller when the buyer fails to fulfill their obligations requires a thorough ethical review. This research employs a qualitative approach with a case study method focusing on companies that implement credit systems in their sales. Data were collected through in-depth interviews with business practitioners and consumers, as well as through the analysis of related documents. The results indicate that although asset repossession in credit sales is recognized as a seller’s right, this practice often conflicts with Sharia principles if it is not carried out with fair consideration for the interests of both parties. The study concludes that there is a need for a more just and transparent mechanism in the repossession process to ensure that the rights of all parties are protected in accordance with Islamic business ethics principles. As a recommendation, it is proposed to develop more detailed ethical guidelines regarding asset repossession in credit sales so that they can be applied consistently and fairly in Sharia business practices.